W miejsce kropek wstaw odpowiednie wyrażenia :

a) (2x + 3y) ( ...... ) = 10 xz+ 4xt + 15yz + 6yt
b) ( x+t ) ( ..... ) = xy + xz - ty - tz
c) ( 3a-b ) ( ...... ) = 18a - 4,5 ac - 6b + 1,5 bc
d) (2x - 5) ( y+6 ) - ........... = 12x - 5y
e) (7-x) (3-y) - ............... = -3x-7y
f) ( 6x-1) (4-y) = y-4 + ..............

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T19:27:17+01:00
A) (2x + 3y) (5z + 2t) = 10 xz+ 4xt + 15yz + 6yt
b) ( x - t ) (y + z) = xy + xz - ty - tz
c) ( 3a-b ) (6 - 1,5c) = 18a - 4,5 ac - 6b + 1,5 bc
d) (2x - 5) ( y+6 ) - 2xy - 30 = 12x - 5y
e) (7-x) (3-y) - 21- xy = -3x-7y
f) ( 6x-1) (4-y) = y-4 + 24x - 6xy
2009-12-08T19:30:06+01:00
A) 5z+2t
b)y+z
c)6+1,5c
d)-2xy+30
e)-21-xy
f)24x-6xy